Bayesian Time Series Modelling Of The Italian Daily Rainfall Data Using Mixed Distribution - Muhammad Safwan Ibrahim; Muhammad Irfan Bin Abdul Jalal (Blue Eyes Intelligence Engineering & Sciences Publication, 2024)
Indexed by SCOPUS